The Psychological Effects of Boy’s Love Fanfiction on the Transformation of Male K-Popers Readers Belief about Same-Gender Romantic Relationships - Azizah, Nur Fuanni; Nur, Haerani (Psikostudia : Jurnal Psikologi, 2025)
Fanfiction is one of the popular media used by K-Popers in the field of literature through digital literacy activities as a means of building imaginative closeness to idols. K-Popers who like reading boy's love fanfiction will make reading activities a hobby that will cause feelings of pleasure and entertainment. Feelings of pleasure and comfort that are felt and sustained can cause addiction and have an impact on changing beliefs. This study aims to determine the process of changing the beliefs of fanfiction boy's love readers towards homosexual love relationships. This research uses a qualitative method with a case study approach. Data was collected through an interview process with two male primary respondents and two significant others as well as screenshots of respondents' social media. The results showed that there was a process of changing the beliefs of readers who were K-Popers and started from curiosity about the content of the story and the attractiveness of the unique storyline also caused respondents to have a great interest in fanfiction boy's love. While reading, the respondents felt the similarity between themselves and the main character of the story, making them fantasize while reading and making reading fanfiction boy's love a hobby and causing celebrity worship, this caused respondents who initially rejected homosexual romantic relationships to accept and start approaching individuals of the same sex and caused a sense of comfort and then decided to have a homosexual romantic relationship.Fanfiction merupakan salah satu media populer yang digunakan K-Popers dalam bidang sastra melalui aktivitas literasi digital sebagai sarana membangun kedekatan imajinatif dengan idola. K-Popers yang menyukai kegiatan membaca fanfiction boy’s love akan menjadikan kegiatan membaca sebagai hobi yang akan menimbulkan perasaan senang dan terhibur. Perasaan senang dan terhibur yang dirasakan dan berkelanjutan dapat menyebabkan kecanduan dan berdampak pada perubahan keyakinan. Penelitian ini bertujuan untuk mengetahui proses perubahan keyakinan pembaca fanfiction boy’s love terhadap hubungan percintaan homoseksual. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Data dikumpulkan melalui proses wawancara kepada dua responden primer berjenis kelamin laki-laki dan dua significant others serta tangkapan layar media sosial responden. Hasil penelitian menunjukkan bahwa terdapat proses perubahan keyakinan pembaca yang merupakan seorang K-Popers dan berawal dari rasa penasaran terhadap isi cerita serta adanya daya tarik alur cerita yang unik juga menyebabkan responden memiliki ketertarikan yang besar pada fanfiction boy’s love. Saat membaca, responden merasakan adanya kesamaan dirinya dengan tokoh utama cerita membuatnya berfantasi saat membaca hingga menjadikan kegiatan membaca fanfiction boy’s love sebagai hobi dan menimbulkan celebrity worship, hal ini menyebabkan responden yang awalnya menolak hubungan percintaan homoseksual menjadi menerima dan mulai melakukan pendekatan dengan individu sesama jenis dan menimbulkan rasa nyaman kemudian memutuskan untuk menjalin hubungan percintaan homoseksual.